Pola koneksi matematis siswa dengan tingkat kemampuan matematika yang berbeda pada materi sistem persamaan linear dua variabel - Hamid, Abdurahman; Juhari, Agusalim (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study aims to analyze the mathematical connection abilities of medium-ability students in solving Two-Variable Linear Equation System (TVLES) problems. Design/methodology/approach: Employing a qualitative descriptive method, this study involved 21 eighth-grade students at SMP Negeri 3 Watampone. Data were gathered through written mathematical connection tests and in-depth interviews with selected medium-ability subjects. Findings: The results reveal a disparity in skills: intra-mathematical connectivity is low (63%) due to barriers in concept integration and analogical reasoning. Conversely, extra-structural connection (mathematics-to-real-life) reached 72%, where students successfully transformed contextual problems into systematic mathematical models. Practical implications: Educators are encouraged to shift from procedural instruction to connection-based learning environments to mitigate conceptual misconceptions among average-achieving students. Originality/value: This study provides specific insights into the